Vocational Schools and Labour Market: Insights from Indonesia - Nofiantoro, W; Affandi, D Y (KnE Social Sciences, 2018)
This article examines the differentiated outcomes of vocational and general secondary academic education, particularly in terms of employment opportunities, labour market earnings, and access to tertiary education in Indonesia. With data from a panel of two waves of the Indonesia Family Life Survey in 1997 and 2000, the article tracks a cohort of high school students in 1997 to examine their schooling and employment status in 2000. The findings demonstrate that: (1) attendance at vocational secondary schools results in neither market advantage nor disadvantage in terms of employment opportunities and/or premium earnings; (2) attendance at vocational schools leads to significantly lower academic achievement as measured by national test scores; and (3) there is no stigma attached to attendance at vocational schools that results in a disadvantage in access to tertiary education; rather, it is the lower academic achievement associated with attendance at vocational school that lowers the likelihood of entering college. Keywords: vocational education, labour market, vocational education